Hubungan Respon Time Perawat Dengan Tingkat Kepuasan Pasien Di Instalasi Gawat Darurat Rumah Sakit Bhayangkara Tk. III Manado - Syafira Makangiras; Faradila M Suranata; Nelfa Fitria Takahepis (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Patient satisfaction is an expression of the patient's feelings for the service received in accordance with the expected service. a fast response time can result in a feeling of satisfaction with the service. The standard time for patients to be served after arriving at the emergency room is ≤ 5 minutes. This can also be achieved by improving the infrastructure, human resources, and management of hospital emergency rooms according to standards. The purpose of this study was to determine the relationship between nurse response time and patient satisfaction in the emergency department of Bhayangkara Hospital, Manado. The research was conducted using analytic observational method with a cross sectional design. Samples were taken based on 43 respondents using non-probabilitay sampling by way of accidental sampling. Measuring tools used in this study were observation sheets and questionnaires. Furthermore, the data were analyzed using the chi-square test with a significant value of ≤ 0.05. The results showed that the p value was smaller than the significant value (0.000 <0.05). The results of this study showed that Ha was accepted and H0 was rejected. The conclusion in this study is that there is a relationship between nurse response time and the level of patient satisfaction in the emergency department of Bhayangkara Hospital, Manado. The results of this study are expected to improve the quality of service in this case the response time of nurses in the emergency department